Comparative study of intraperitoneal adhesions related to light-weight polypropylene mesh and type I polymerized and purified bovine collagen coated light-weight polypropylene mesh in rabbits - Garcia,Diego Paim Carvalho (2017)
Abstract Purpose: To compare the effectiveness of light-weight polypropylene mesh coated with polymerized and purified bovine type I collagen (Surgidry HNB) in the treatment of abdominal wall defect and the degree of adhesion formation. Methods: Two types of polypropylene mesh were implanted after creation of defect measuring 6.0cm X 5.5cm in the anterior abdominal wall of 32 male New Zealand breed rabbits, divided in two groups (n = 32): (1) light-weigh macroporous polypropylene, (2) type I polymerized and purified bovine collagen coated light-weigh macroporous polypropylene. These animals were further accessed for adhesions, histological evaluation of inflammation and wall’s thickness. Results: The percentage of the area adhered in group 1 (62.31 ± 16.6) was higher compared to group 2 (22.19 ± 14.57) (p <0.05). There was an association between the percentage of the covered area by adhesions and the type of adhesion, toughness and the scores obtained by the adhesion score by correlation analysis (p <0.05). There was no difference between the groups in any variables in relation to the degree of inflammation. Conclusion: The purified type I bovine collagen coated light-weigh polypropylene mesh showed to be effective in the repair of abdominal wall defects and reducing adhesion formation.